Detection of Integron Classes and Agr Group in Staphylococcus aureus Isolated from Different Clinical Samples - Zaid Tariq Ahmed, Rasha; Abdullah, Rana Mujahid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Fifty isolates of Staphylococcus aureus were obtained out of 220 samples collected from clinical sources after a diagnosis of the bacteria, and then a sensitivity test was performed for the isolates, and the minimum inhibitor concentration of 15 antibiotics in the bacterial isolates under study was determined using the Vitek -2 Compact System device. All isolates showed 100% resistance to Benzylpenicillin at (>=0.5-0.12) and the resistance to Oxacillin was 76% at (>= 1-4), Ciprofloxacin and Moxifloxacin was 42, 40% at (>=2-8), Gentamycin (20%) at >=16, Erythromycin by (78%) at >=8, Clindamycin (by 74%) at (>=8-16), Tetracycline by 40% at (>=2-16), Fusidic Acid by (14%) at (>=8-32), and Rifampicin by (6% ) at of (>=32 and Trimethoprim/ Sulfamethoxal by 14% at a concentration of (>=80-320). The isolates also showed less resistance to Vancomycin, Linezolid, and Teicoplanin (5, 2, and 2%), respectively, at a concentration of >=32 and all isolates were sensitive to Tigecycline (100%). Genomic DNA was extracted for the bacterial isolates under study and revealed that the bacteria possessed the integron. The results showed that S. aureus bacteria had the genes of the integron (intI1, intI2, intI3) using a specific promoter. The results showed that the most commonly found genes in S. aureus bacteria were the intI1 gene by 41 (82%), followed by the intI2 gene (5%). All isolates gave a negative result for the intI3 gene. The result of molecular typing using the agr method showed that the percentage of the presence of the genes agr1, agr2, and agr3 for S. aureus bacteria was 88, 6, and 35%, respectively, and all the isolates under study showed that they did not contain the agr4 gene.